Modern control systems - Dorf, Richard C. (Pearson, 2017)
The thirteenth edition continues to explore the role of and need for automated and precise control systems in green engineering. Key examples of green engineering, such as wind turbine control and the modelling of a photovoltaic generator to achieve maximum power delivery, are discussed in detail. The text is organised around the concept of control systems theory in the context of frequency and time domains.